Performance Evaluation and Fouling Propensity of Forward Osmosis (FO) Membrane for Reuse of Spent Dialysate - Kim, Chaeyeon (Membranes (Basel), 2020)
The number of chronic renal disease patients has shown a significant increase in recent decades over the globe. Hemodialysis is the most commonly used treatment for renal replacement therapy (RRT) and dominates the global dialysis market. As one of the most water-consuming treatments in medical procedures, hemodialysis has room for improvement in reducing wastewater effluent. In this study, we investigated the technological feasibility of introducing the forward osmosis (FO) process for spent dialysate reuse. A 30 LMH of average water flux has been achieved using a commercial TFC membrane with high water permeability and salt removal. The water flux increased up to 23% with increasing flowrate from 100 mL/min to 500 mL/min. During 1 h spent dialysate treatment, the active layer facing feed solution (AL-FS) mode showed relatively higher flux stability with a 4–6 LMH of water flux reduction while the water flux decreased significantly at the active layer facing draw solution (AL-DS) mode with a 10–12 LMH reduction. In the pressure-assisted forward osmosis (PAFO) condition, high reverse salt flux was observed due to membrane deformation. During the membrane filtration process, scaling occurred due to the influence of polyvalent ions remaining on the membrane surface. Membrane fouling exacerbated the flux and was mainly caused by organic substances such as urea and creatinine. The results of this experiment provide an important basis for future research as a preliminary experiment for the introduction of the FO technique to hemodialysis.